PENGARUH PELEBARAN JALAN PADA KAWASAN U-TURN (PUTAR BALIK ARAH) TERHADAP KINERJA ARUS LALU LINTAS STUDI KASUS RUAS JALAN AHMAD YANI II PONTIANAK (JALAN ARTERI SUPADIO) KABUPATEN KUBU RAYA) - Fredi, -; Akhmadali, -; Kadarini, Siti Nurlaily (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
Efforts to minimize the problem of traffic movement, especially on the security and the key on the road can be done by making the median. in the median planning is also provided a median opening which allows the vehicle to change the direction of travel in the form of a reversing direction or termed as u-turn motion. The purpose of this study is to evaluate the traffic characteristics of widening or adding lane in the u-turn region, analyzing the average travel time and delay time due to the u-trun activity on the road. In this thesis reviewed as the object of research is u-turn without widening and u-turn with widening as comparison, to know how big geometric influence u-turn on Ahmad Yani II road (Jalan Ateri Supadio) to traffic flow performance then need analysis of speed and delay due to u-turn activity. The research methodology used in this paper is a descriptive methodology that is a problem solving procedure examined by describing the state of the object of research at the present moment based on facts in place or as it is. Data used for analysis by means of primary collection consisting of road geometric , travel time, and delay. Secondary obtained from a number of reports and documents that have been prepared by relevant agencies and other literary study results. Based on the results of the survey and conducted the analysis then obtained the following conclusions delay average u-turn without widening is equal to 57.7 seconds and the average speed is equal to 24.27 km / h, the average delay u-turn with widening is 10.66 seconds and the average speed is 46.75 km / hour. Judging from the above analysis it is known that u-turn without widening has greater disturbed time compared to u-turn with widening.Â Â Keyword : U Turn